PERILAKU AKSES MODAL DAN PEMBAYARAN UMKM BORDIR DAN KONVEKSI ANGGOTA KSU PADURENAN JAYA KUDUS - Indriastuti, Ariyani (JURNAL STIE SEMARANG, 2016)
This research objectiveis to determine and describe the capital assessment behaviour of Padurenan SMEs. Phenomenology design is expected to reveal  phenomenon in this research.  Data obttained is derived from three informants by using snow ball method. Unigue payment system base on trust relationships (nota berjalan) is use by SMEs Padurenan Jaya Kudus. SMEs can deliver raw material and term of payment  cant not fixed about this time and the amount. Total liabilities will be paid by SMEs in “Ruwah month”. Complicated method unacceptable in formal banking system. This behaviour is an obstacle in forming a close relationship of acces capital between banking system and SMEs.